Revision of the Melanogaster jaroslavensis group (Diptera: Syrphidae), with description of a new species from Afghanistan - Popov, Grigory V.; Prokhorov, Alexey V.; Kustov, Semen Yu. (Zootaxa, 2020)
Within the genus Melanogaster Rondani, 1857, the group of species characterized by their yellow wing base was named as M. jaroslavensis group and revised for the first time. Redescriptions of M. jaroslavensis (Stackelberg, 1922), M. kirgisorum (Stackelberg, 1952), and M. tadzhikorum (Stackelberg, 1952) are provided. A new species of the M. jaroslavensis group, Melanogaster raccoon sp. nov., from Afghanistan, is described. The male of this new species differs from those of other known Melanogaster species by the following combination of characters: yellowish wing base, pale body pile, without dark pile, almost flat face, and surstyli short and emarginated apically in ventral view. Females of M. raccoon sp. nov. differ from those of any other Melanogaster species by a combination of yellowish wing base and frons without transverse furrows. An identification key to the species of the M. jaroslavensis group is presented.